Day 2 Thu, October 20, 2016 2016
DOI: 10.2118/181154-ms
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate is Your Well Integrity? A Discussion About the Surface Casing Integrity Under Temperature Loading in Heavy Oil Fields

Abstract: In various parts of the world, heavy oil projects use high temperatures in order to support the oil production. Most of these projects are still on-going after several years of high temperature well exposure, while others have been suspended due to operational and environmental issues. The well integrity time span should extend itself beyond the field estimated operational date. These wells (observation, productions or abandoned) are highly susceptible to leaks due to cement degradation resulting from thermo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The steam temperature may easily exceed 200 °C and could reach 350 °C, under pressure that could reach 6 MPa (Placido et al, 1997;Dean and Torres, 2002;Alvarez and Han, 2013). The heating process generated by steam injection can induce extreme thermal stresses in the well, which, when combined to mechanical stresses, may cause: (i) plastic yielding and/or buckling of the steel casing (Placido et al 1997;Peng et al, 2007;Li, 2008;Ferla et al, 2009), and (ii) cracking or failure of the cement sheath and/or its debonding from the casing and surrounding rock formation (Dean and Torres, 2002;Garnier et al, 2010;De Bruijn et al, 2010;Teodoriu et al, 2013;Yuan et al, 2013;Wang and Taleghani, 2014;Lavrov et al, 2015;Shadravan et al, 2015;Ichim et al, 2016). A damaged cement sheath can favor leakage of hydrocarbonates to the rock formation, where they may propagate through geological strata to reach aquifers or the surface, thus causing significant environmental degradation, and calling for expensive remedial measures (Thiercelin et al, 1998;Nelson and Guillot, 2006;Bellabarba et al, 2008;Dusseault and Jackson, 2014;Lavrov et al, 2015;Zhang et al, 2015;Abimbola et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The steam temperature may easily exceed 200 °C and could reach 350 °C, under pressure that could reach 6 MPa (Placido et al, 1997;Dean and Torres, 2002;Alvarez and Han, 2013). The heating process generated by steam injection can induce extreme thermal stresses in the well, which, when combined to mechanical stresses, may cause: (i) plastic yielding and/or buckling of the steel casing (Placido et al 1997;Peng et al, 2007;Li, 2008;Ferla et al, 2009), and (ii) cracking or failure of the cement sheath and/or its debonding from the casing and surrounding rock formation (Dean and Torres, 2002;Garnier et al, 2010;De Bruijn et al, 2010;Teodoriu et al, 2013;Yuan et al, 2013;Wang and Taleghani, 2014;Lavrov et al, 2015;Shadravan et al, 2015;Ichim et al, 2016). A damaged cement sheath can favor leakage of hydrocarbonates to the rock formation, where they may propagate through geological strata to reach aquifers or the surface, thus causing significant environmental degradation, and calling for expensive remedial measures (Thiercelin et al, 1998;Nelson and Guillot, 2006;Bellabarba et al, 2008;Dusseault and Jackson, 2014;Lavrov et al, 2015;Zhang et al, 2015;Abimbola et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The casing failures in this case are mainly due to combined influence of high internal pressure due to injection and high steam temperatures; stresses often exceed elastic limit of typical thermal well casing materials. Also, Ichim and Teodoriu (2016) study noted that cyclic stresses during heavy oil recovery negatively affect the well mechanical response leading to well integrity issues. Kaldal et al (2015) indicated that large and rapid wellbore temperature changes in high temperature and or geothermal wells during production and stimulation, produce large thermal stresses in the production casing which can cause casing failures.…”
mentioning
confidence: 99%